Copper removal from aqueous solutions by sugar beet pulp treated by NaOH and citric acid - Altundoğan, Hamdi Soner (My University, 2007)
Sugar beet pulp was converted into effective copper sorption material by treating subsequently with NaOH and citric acid. Compared with the untreated sugar beet pulp, the cation exchange capacity of the modified sugar beet pulp increased from 0.86 to 3.21 mequiv. g?1. Swelling capacity and COD values of modified sugar beet pulp were found to be decreased in the ratio of 38% and 61%, respectively, compared to the corresponding values of native sugar beet pulp, meaning that modification causes stabilization. Sorption characteristics of the modified sugar beet pulp towards copper ions were studied with batch experiments. Pseudo-first, pseudo-second-order and intraparticle kinetic models were applied to the kinetic data and it was found that the sorption processes followed the pseudo-second-order rate kinetics with activation energy of 16.34 kJ mol?1. The equilibration data fit best with the Langmuir isotherm the maximum copper sorption capacity of which is 119.43 mg g?1. The mean free energy of copper sorption process calculated from Dubinin–Radushkevich model and the Polanyi potential concept was found to be in the range of 10.91–11.95 kJ mol?1 showing that the main mechanism governing the sorption process is ion exchange. The negative values found for enthalpy change (?14.797 kJ mol?1 over the range of 25–55 °C) and free energy change (?19.361 kJ mol?1 for 25 °C) indicate that the sorption process is exothermic and spontaneous in nature.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Modified sugar beet pulp; NaOH; Citric acid; Copper sorption characteristics